Visualization of electro-physical and chemical machining processes. Issue 2 (2019) - Kunieda, Masanori; Overmeyer, Ludger; Klink, Andreas
Abstract: This paper aims to visualize spatio-temporal phenomena in electro physical and chemical processes in order to understand machining mechanisms and to achieve a technological breakthrough. In situ measurement methods to visualize the time evolution of stress, strain, temperatures, fluid velocities, and species density distributions, together with 2D or 3D images of the workpieces being processed are summarized. Applications of these methods to fundamental studies on electrical discharge machining, electrochemical machining, laser processing and additive manufacturing are introduced. Signal recording and processing technologies and real time monitoring enabling closed-loop feedback control are also discussed.